2022
DOI: 10.1152/ajpendo.00429.2021
|View full text |Cite
|
Sign up to set email alerts
|

Circulating insulin-like growth factor system adaptations in hibernating brown bears indicate increased tissue IGF availability

Abstract: Brown bears conserve muscle and bone mass during six months of inactive hibernation. The molecular mechanisms underlying hibernation physiology may have translational relevance for human therapeutics. We hypothesize that protective mechanisms involve increased tissue availability of the insulin-like growth factors (IGFs). In subadult Scandinavian Brown Bears, we observed that mean plasma IGF-1 and IGF-2 during hibernation was reduced to 36±10% and 56±15%, respectively, compared to the active state (N=12). West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…We also found that the serum IGF-1 level was significantly higher in Arctic foxes than in silver foxes. This finding is in line with previous findings that plasma IGF-1 is increased in the reindeer and brown bear during the accumulation of fat depots (19,20). IGF-1 can also induce lipid synthesis through the PI3K-Akt signaling pathway (37, 38).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that the serum IGF-1 level was significantly higher in Arctic foxes than in silver foxes. This finding is in line with previous findings that plasma IGF-1 is increased in the reindeer and brown bear during the accumulation of fat depots (19,20). IGF-1 can also induce lipid synthesis through the PI3K-Akt signaling pathway (37, 38).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, insulin-like growth factor 1 (IGF-1) produced in the liver not only mediates glycogen synthesis (17) but also functions as a critical hormone for fuel metabolism, increasing glucose tolerance and insulin sensitivity in mice (18). Further evidence for the role of IGF-1 in lipid metabolism includes the significant increase in plasma IGF-1 during the period of rapid weight gain in the reindeer (19) and brown bear during the nonhibernation period when fat depots accumulate (20).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the serum IGF-1 level was significantly higher in Arctic foxes than in silver foxes. This finding is in line with previous findings that plasma IGF-1 is increased in the reindeer and brown bear during the accumulation of fat depots (19,20). IGF-1 can also induce lipid synthesis through the PI3K-Akt signaling pathway (37, 38).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, insulin-like growth factor 1 (IGF-1) produced in the liver not only mediates glycogen synthesis (17) but also functions as a critical hormone for fuel metabolism, increasing glucose tolerance and insulin sensitivity in mice (18). Further evidence for the role of IGF-1 in lipid metabolism includes the significant increase in plasma IGF-1 during the period of rapid weight gain in the reindeer (19) and brown bear during the nonhibernation period when fat depots accumulate (20).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, insulin-like growth factor 1 (IGF-1) produced in the liver not only mediates glycogen synthesis ( 17 ) but also functions as a critical hormone for fuel metabolism, increasing glucose tolerance and insulin sensitivity in mice ( 18 ). Further evidence for the role of IGF-1 in lipid metabolism includes the significant increase in plasma IGF-1 during the period of rapid weight gain in the reindeer ( 19 ) and brown bear during the nonhibernation period when fat depots accumulate ( 20 ).…”
Section: Introductionmentioning
confidence: 99%